APPLICATION OF ADDITIVE TECHNOLOGIES IN THE CREATION OF METAMATERIALS WITH ADJUSTABLE DIELECTRIC PROPERTIES - САВЧЕНКО, Б. М.; СОВА, Н. В.; ХОМЕНКО, В. Г.; СЛЄПЦОВ, О. О.; БУЛГАКОВ, Є. С.; СЛЄПЧЕНКО, Р. Ю. (Technologies and Engineering, 2024)
Purpose. The purpose of this article is to study the influence of the programmable infill structure of material obtained by the additive manufacturing method on their dielectric properties. Methodology. The dielectric characteristics of the test samples were studied by measuring their capacitance and dielectric loss tangent using the RLC meter according to a 4-electrode scheme. The measurements were carried out using alternating current and measuring frequencies of 100 Hz, 1-10-100 kHz. Findings. The relative permittivity is linearly dependent on the specific density and degree of volume filling with high reliability and varies slightly with the measurement frequency. An increase in temperature can change the value of the relative permittivity only in the case of monolithic samples by 2.5% at a temperature of 50℃. The values of the relative permittivity calculated by theoretical models coincide with the measured values for all values of the volume filling. The use of software filling makes it possible to effectively vary the relative permittivity of polylactide material. Originality. It was found that the relative dielectric constant of the polylactide samples under study has a linear dependence on the degree of volume filling. Practical value. It has been established that the use of software filling of prototypes during additive manufacturing allows the creation of materials with adjustable values of the relative permittivity for the creation of products for radio frequency applications.